Manajemen Risiko Berbasis ISO 31000: Studi Kasus UMKM Fashion “Benang Baju” di Kota Bandung - Fatimah Rahman; Afrian Insan Kamil; Maliha Rizka Humaira; Susi Nurohimah; Alfiana (Indo Publishing, 2025)
This study examines Benang Baju, a local fashion MSME (Micro, Small, and Medium Enterprise) based in Bandung City, which focuses on producing minimalist-style casual clothing. The purpose of this research is to identify, analyze, and evaluate various potential risks that may hinder the achievement of business objectives, as well as to determine appropriate risk treatment strategies based on the evaluation results. This study applies a Descriptive Qualitative method combined with the ISO 31000 risk management framework, covering stages of risk identification, analysis, evaluation, and treatment. A 5×5 Risk Management Matrix is also utilized to assess the likelihood and impact levels of each identified risk event. The findings reveal 6 main risk categories with a total of 20 risk events, consisting of 12 events classified as medium risk level, 1 event as low risk level, and 7 events as high risk level requiring special attention. The high-risk events include R01 (rapid changes in fashion trends), R02 (intense competition among local brands), R03 (decline in consumer purchasing power), R09 (fluctuations in fabric prices), R11 (delays in raw material supply from vendors), R15 (production overload during high demand periods), and R16 (shortage of skilled labor). The implementation of the ISO 31000 framework has proven effective in helping Benang Baju systematically manage risks, enhance business resilience, and strengthen competitiveness within the dynamic local fashion industry.